The Central Role of Amino Acids in Cancer Redox Homeostasis: Vulnerability Points of the Cancer Redox Code - Vučetić, Milica; Cormerais, Yann; Parks, Scott K.; Pouysségur, Jacques (Frontiers in Oncology, 2017)
A fine balance in reactive oxygen species (ROS) production and removal is of utmost importance for homeostasis of all cells and especially in highly proliferating cells that encounter increased ROS production due to enhanced metabolism. Consequently, increased production of these highly reactive molecules requires coupling with increased antioxidant defense (AOD) production within cells. This coupling is observed in cancer cells that allocate significant energy reserves to maintain their intracellular redox balance. Glutathione (GSH), as a first line of defense, represents the most important, non-enzymatic antioxidant component together with the NADPH/NADP+ couple, which ensures the maintenance of the pool of reduced GSH. In this review, the central role of amino acids in the maintenance of redox homeostasis in cancer, through GSH synthesis (cysteine, glutamate, and glycine), and NAD(P)H production (serine, and glutamine/glutamate) are illustrated. Special emphasis is placed on the importance of amino acid transporters known to be up-regulated in cancers (such as xCT and ASCT2) in the maintenance of amino acid homeostasis, and thus indirectly, the redox homeostasis of cancer cells. The role of the ROS varies (often described as a ‘two-edged sword’) during the processes of carcinogenesis, metastasis and cancer-treatment. Therefore the context-dependent role of specific amino acids in the initiation, progression and dissemination of cancer, as well as in the redox-dependent sensitivity/resistance of the neoplastic cells to chemotherapy are highlighted.